A Delta-V map of the known Main Belt Asteroids. (May 2018) - Taylor, Anthony; McDowell, Jonathan C.; Elvis, Martin
Abstract: With the lowered costs of rocket technology and the commercialization of the space industry, asteroid mining is becoming both feasible and potentially profitable. Although the first targets for mining will be the most accessible near Earth objects (NEOs), the Main Belt contains 10 6 times more material by mass. The large scale expansion of this new asteroid mining industry is contingent on being able to rendezvous with Main Belt asteroids (MBAs), and so on the velocity change required of mining spacecraft (delta-v). This paper develops two different flight burn schemes, both starting from Low Earth Orbit (LEO) and ending with a successful MBA rendezvous. These methods are then applied to the ∼ 700, 000 asteroids in the Minor Planet Center (MPC) database with well-determined orbits to find low delta-v mining targets among the MBAs. There are 3986 potential MBA targets with a delta-v < 8 km s − 1, but the distribution is steep and reduces to just 4 with delta-v < 7 km s -1 . The two burn methods are compared and the orbital parameters of low delta-v MBAs are explored. Highlights: Two orbital burn methods for rendezvous with Main Belt asteroids are developed. The methods are applied to the MPC dataset, solving for rendezvous delta-v. Orbital characteristics of low delta-v Main Belt asteroids are analyzed. A list of the lowest delta-v Main Belt asteroids is presented.